2022
DOI: 10.2298/jsc211203057p
|View full text |Cite
|
Sign up to set email alerts
|

25 years of NICS - much more than nothing!

Abstract: The famous aromaticity index NICS (Nucleus Independent Chemical Shift) was introduced 25 years ago. The authors use this anniversary for a short and incomplete personal retrospect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…[38] One of the most well-known magnetic indexes in measuring the aromaticity of rings is the nucleus-independent chemical shift (NICS). [37,39] Reversing the sign of the magnetic shielding at a ring center gives the NICS value of the ring. Negative NICS values mean aromatic and positive for antiaromatic.…”
Section: Organic Bases Have Received Considerable Attention Due To Theirmentioning
confidence: 99%
“…[38] One of the most well-known magnetic indexes in measuring the aromaticity of rings is the nucleus-independent chemical shift (NICS). [37,39] Reversing the sign of the magnetic shielding at a ring center gives the NICS value of the ring. Negative NICS values mean aromatic and positive for antiaromatic.…”
Section: Organic Bases Have Received Considerable Attention Due To Theirmentioning
confidence: 99%
“…It has been demonstrated that NICS values calculated for osmabenzenes are dominantly influenced by the local currents around the metal atom . Thus, the single-point NICS index, which is one of the most employed aromaticity measurements, is not a reliable tool for analyzing the metallabenzenes aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…Gerothanassis et al published two review papers on DFT prediction of d( 13 C) and d( 1 H) chemical shifts and 3 J( 13 C-O-O-1 H) coupling constants used in structural studies on hydroperoxides. 18,19 An interesting review on calculation and applications of magnetic index of aromaticity, nuclear independent chemical shift (NICS) was published by Puchta et al 20 Intermolecular interactions are of utmost importance in both natural producs and material science and NMR is a very useful tool in their experimental and theoretical characteristic.…”
Section: Introductionmentioning
confidence: 99%